Omnivorous religions: Chané shamanism and inter-ethnic relationships - Villar, Diego (2007)
Of Arawak origin, the ethnic group identified as the Chané indigenous group in the Amerindian literature, settled on the eastern slopes of the Andes before the Conquest of the Occidental region or Paraguayan Chaco took place. There, this group engaged in complex inter-ethnic relationships with other Guarani-speaking ethnic groups, Chaco natives, and thereafter, as the colonization process consolidated, with several Creole social agents: landowners, foremen of sugar plantations, the military, and missionaries. Supported by ethnographic and ethno-historical documents, the author suggests that the open, flexible, malleable and integrating organization of Chané shamanism was marked by these multiple historical interactions, thereby becoming an ideal symbolic language to reflect the problems arising from situations of intercultural contact.